Establishing AICCRA demonstration fields to improve adoptive capabilities of farmers to address climate change in the Kumbungu District of the northern region of Ghana – A field day - Masoud, Jalaludeen; Ofosu-ampong, Kingsley; Amankwaa-Yeboah, Patricia; Akpatsu, Isaac Boatey; Salifu, Fuseini; Abera, Wuletawu (2024)
As Northern Ghana faces prolonged droughts exacerbated by climate change, there is an urgent need for farmers to adopt climate-resilient strategies to mitigate the devastating impacts and ensure sustainable agriculture. This report highlights the effectiveness of maize-cowpea intercropping and ridging in conserving soil moisture by reducing water loss through transpiration and suppressing weeds. Farmers were also encouraged to adopt drought-tolerant varieties and apply basal fertilizer at planting, shifting from the traditional practice of applying it 10-14 days later. Achieving the optimal plant population is another key factor in improving yields. To aid this, farmers were introduced to the push planter, which helps ensure the correct plant population while reducing labor. In the demonstration areas, the drought lasted between 35 and 40 days. Continuous monitoring and evaluation of these practices are essential for promoting long-term agricultural sustainability and food security in the region.